Analysis of Consumer Trust in Direct Transaction Methods via WhatsApp in “Take on Thrift” Online Shop - Luis, Lydia Kharis; Sanjaya, Regi (Dinasti Publisher, 2025)
This study aims to analyze the factors influencing consumer trust in direct transactions via WhatsApp at the